ENVIRONMENTAL EFFECT ON SUGARCANE LEAF MITE, SCHIZOTETRANYCHUS ANDROPOGONI (HIRST) ON SUGARCANE ECO-SYSTEM - BAIRWA , BIRBAL; R. N. SINGH (The Bioscan, 2013)
Field experiment was carried out during 2011 on effect of weather factors on sugarcane leaf mite, Schizotetranychus andropogoni (Hirst.) on sugarcane eco-system. The population was observed till the mite population occurs. The maximum mean population of egg and nymph 7.59 and 3.36 was recorded per colony per leaf in the month of June 2011. The maximum mean population of adult mite 5.22 was recorded in the last week of July 2011. The non-significant relation was observed in adult mite influence in respect to temperature (-2.51) and rainfall (0.44). The significant relation was recorded in mean relative humidity (4.80). The webs size showed significant influence of temperature (3.51) and non significant relation in relative humidity (-2.65) and rainfall (-2.02). The population of mites per colony performed significant relation in relative humidity and mean temperature and total rainfall showed non significant relation. Relative humidity and temperature appeared to be regulatory factor for mite population. The overall conclusions the temperature and relative humidity have great influence in the population buildup this mite.